2019
DOI: 10.4236/ajibm.2019.911134
|View full text |Cite
|
Sign up to set email alerts
|

Lean Mining, Productivity and Occupational Health and Safety: An Expert-Elicitation Study

Abstract: The implementation of lean tools in the Canadian mining industry is still in its beginnings. To the best of our knowledge, published information and articles on this subject are scarce. Consequently, the impacts of using lean tools on productivity and workers' health and safety in this field are still unclear and need more investigations to better integrate the technical aspects of lean with Occupational Health and Safety (OHS). Therefore, this study aims to provide insights about lean mining in Canada. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The implementation of improvement initiatives such as lean in the mining sector has been studied previously using lean tools such as kaizen, value stream mapping (VSM), total productive maintenance (TPM), and single minute exchange die (SMED). The focus of these studies was on the gold mining companies in Canada and the results showed a positive impact of the tools on productivity and work safety (Nemati et al 2019). Another study also discussed the challenges in coal mining operations (Yu et al 2016) and those observed to be prevalent include low productivity, low efficiency, safety, and environmental issues (Maunzagona and Telukdarie 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of improvement initiatives such as lean in the mining sector has been studied previously using lean tools such as kaizen, value stream mapping (VSM), total productive maintenance (TPM), and single minute exchange die (SMED). The focus of these studies was on the gold mining companies in Canada and the results showed a positive impact of the tools on productivity and work safety (Nemati et al 2019). Another study also discussed the challenges in coal mining operations (Yu et al 2016) and those observed to be prevalent include low productivity, low efficiency, safety, and environmental issues (Maunzagona and Telukdarie 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The term "Overall Equipment Effectiveness (OEE)" was first introduced by (Nakajima 1988) as an indicator of manufacturing equipment productivity. It has been used to measure the success of implementing the total productive maintenance (TPM) program (Cheah et al 2020) and also as a standard indicator to evaluate production productivity (Soltanali and Khojastehpour 2021;Chikwendu et al 2020;Ng et al 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation